Effects of jaw exercise intervention timing on outcomes following oral and oropharyngeal cancer surgery: Pilot study. Issue 11 (12th August 2019) - Sandler, Mykayla L.; Lazarus, Cathy L.; Ru, Meng; Sharif, Kayvon F.; Yue, Lauren E.; Griffin, Martha J.; Likhterov, Ilya; Chai, Raymond L.; Buchbinder, Daniel; Urken, Mark L.; Ganz, Cindy
Abstract: Background: Common in head and neck cancer patients, trismus can make speech and swallowing difficult and can compromise quality of life (QOL). Jaw range of motion exercise therapy may prevent or treat trismus in surgical patients. While the importance of these exercises is well‐documented, there is little literature regarding the optimal timing of exercise initiation. Methods: A prospective pilot study investigated the effects of early vs late jaw exercise intervention on postoperative jaw opening and QOL measures, which were examined descriptively. Results: Timing of exercise intervention was not found to significantly impact the measured outcomes. However, provisional, descriptive findings showed that jaw opening was significantly associated with multiple QOL measures, with greater jaw opening associated with improved QOL. For certain QOL measures, this positive association was stronger at earlier time points than at later time points. Conclusions: The exploratory findings of this pilot study support further research into possible benefits of early jaw exercise intervention.